The genus Vitex: A review - Rani, Anita; Sharma, Anupam (Pharmacognosy Reviews)
The review includes 161 references on the genus Vitex, and comprises ethnopharmacology, morphology and microscopy, phytoconstituents, pharmacological reports, clinical studies, and toxicology of the prominent species of Vitex. Essential oils, flavonoids, iridoid glycosides, diterpenoides and ligans constitute major classes of phytoconstituents of the genus. A few species of this genus have medicinal value, among these, leaves and fruits of V. agnus‑castus Linn. (Verbenaceae) has been traditionally used in treatment of women complaints. V. agnus‑castus has also been included in herbal remedies, which are in clinical use to regulate the menstrual cycle, reduce premenstrual symptom tension and anxiety, treat some menopausal symptoms as well as to treat hormonally induced acne. Despite a long tradition of use of some species, the genus has not been explored properly. In the concluding part, the future scope of Vitex species has been emphasized with a view to establish their multifarious biological activities and mode of action.
Keywords: Diterpenoides; essential oils; flavonoids; iridoid glycosides; vitex agnus‑castus